Islamic legal analysis of pay-later usage as an electronic transaction - Sri Maskanah; Wargo; Kuswanto (Zabags International Journal of Islamic Studies, 2025)
The rapid expansion of financial technology in Indonesia has propelled the popularity of buy now pay later (BNPL) services, notably Shopee PayLater, which enable deferred payments for electronic transactions while raising legal and ethical concerns from an Islamic law perspective due to interest charges and late-payment penalties. This study examines how PayLater operates as an instrument for electronic transactions and evaluates its compliance with Islamic legal principles. Adopting a Systematic Literature Review (SLR) approach, the analysis synthesizes academic literature, national regulations, and relevant Sharia fatwas. Findings indicate that, although PayLater fosters digital financial inclusion, monthly interest and late-payment penalties are inconsistent with the core structures of qardh (interest-free loans) and bai’ al-taqsith (credit sales with predetermined prices), and potentially contravene maqasid al-sharia, particularly the protection of wealth (hifz al-mal). The article advances theory by reinforcing Islamic law as a robust framework for assessing contemporary fintech, and offers practical guidance for regulators and providers to develop Sharia-compliant PayLater models grounded in fairness, transparency, and sustainability. These results also underscore the need for future empirical and cross-jurisdictional research on Islamic fintech regulation.